Ultrasound-assisted enzymatic synthesis of poly-ε -caprolactone: kinetic behavior and reactor design - Gumel, A.M.; Annuar, M.S.M.; Chisti, Y. (2013)
Lipase-mediated, ultrasound-assisted synthesis of poly-ε-caprolactone was investigated. It was found that ultrasound irradiation helped to improve the rate constant of poly-ε-caprolactone chain propagation (kp) at high initial monomer (ε-caprolactone) concentration. The enhancement of kp ranged from 34% to 46% at 22.5– 18.0 M initial monomer concentration, respectively. In a system proned to time-dependent mass-transfer limitation due to polymer chain extension, the acoustic effects could have also allowed the reaction to continue longer compared to non-sonicated process until it became impossible at highly elevated reaction mixture viscosity (>2,000 times increase from initial viscosity). Consequently, it also helped to improve monomer conversion. In a continuous flow polymerization system, a plug flow reactor system is recommended due to its lowest volume for maximum conversion compared to a continuously stirred tank reactor system.